Site testing campaign for the Large Optical/infrared Telescope of China: overview - Feng, Lu; Hao, Jin-Xin; Cao, Zi-Huang; Bai, Jin-Min; Yang, J; Zhou, Xu; Yao, Yong-Qiang; Hou, Jin-Liang; Zhao, Yong-Heng; Liu, Yu; Song, Teng-Fei; Liu, Li-Yong; et al. (Research in astronomy and astrophysics, 2020)
The Large Optical/infrared Telescope (LOT) is a ground-based 12 m diameter optical/infrared telescope which is proposed to be built in the western part of China in the next decade. Based on satellite remote sensing data, along with geographical, logistical and political considerations, three candidate sites were chosen for ground-based astronomical performance monitoring. These sites include: Ali in Tibet, Daocheng in Sichuan and Muztagh-ata in Xinjiang. Up until now, all three sites have continuously collected data for two years. In this paper, we will introduce this site testing campaign, and present its monitoring results obtained during the period between March 2017 and March 2019.